Development and evaluation of immunoassay for detection of antibodies to the feline T-lymphotropic lentivirus (feline immunodeficiency virus). - O'Connor, T P (1989)
The feline T-cell lymphotropic lentivirus (feline immunodeficiency virus) is a recently described feline-specific retrovirus that can produce chronic immunodeficiency-like disorders in cats. A microdilution plate format enzyme-linked immunosorbent assay has been developed to detect the presence of antibody to the virus in feline serum or plasma. Temporal studies performed with experimentally infected animals show that seroconversion can be demonstrated 3 to 4 weeks after exposure to the virus. Results of a serosurvey (n = 1,556 samples) indicate that infection is fairly common in both clinic (5.2%) and sick cat (15.2%) populations. Western blot (immunoblot) and sodium dodecyl sulfate radioimmunoprecipitation assays were developed to confirm microdilution plate test results and to identify peptides specific for the feline immunodeficiency virus. All microdilution plate test positive results and selected negative results were confirmed by one or both of these procedures. These data demonstrate that this microassay plate enzyme-linked immunosorbent assay is a very sensitive and specific test for detection of antibody to the feline immunodeficiency virus.